2020
DOI: 10.1093/jxb/eraa143
|View full text |Cite|
|
Sign up to set email alerts
|

High-throughput phenotyping using digital and hyperspectral imaging-derived biomarkers for genotypic nitrogen response

Abstract: The development of crop varieties with higher nitrogen use efficiency is crucial for sustainable crop production. Combining high-throughput genotyping and phenotyping will expedite the discovery of novel alleles for breeding crop varieties with higher nitrogen use efficiency. Digital and hyperspectral imaging techniques can efficiently evaluate the growth, biophysical, and biochemical performance of plant populations by quantifying canopy reflectance response. Here, these techniques were used to derive automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 60 publications
2
47
0
Order By: Relevance
“…Our results show that overall, high-throughput image-based phenotyping techniques can be used to screen large germplasm populations, and identify candidate genotypes for further field evaluations. This protocol fits with previous research which has also demonstrated that early vegetative screens can provide insight into the performance and yield of germplasm at later stages (Krishnamurthy et al, 2007;Meng et al, 2017) or under stresses (Nguyen et al, 2019;Banerjee et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results show that overall, high-throughput image-based phenotyping techniques can be used to screen large germplasm populations, and identify candidate genotypes for further field evaluations. This protocol fits with previous research which has also demonstrated that early vegetative screens can provide insight into the performance and yield of germplasm at later stages (Krishnamurthy et al, 2007;Meng et al, 2017) or under stresses (Nguyen et al, 2019;Banerjee et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…This suggests that ESB can be effectively used to estimate fresh and dry biomass, obviating the need for destructive harvesting. Biomass at vegetative stages, under abiotic stresses, have been shown to highly correlate to biomass production at maturity, illustrating that performance in vegetative screens is a good indicator of performance at yield (Nguyen et al, 2019;Banerjee et al, 2020). Biomass-based traits show high narrow-sense heritability, although they are controlled by additive gene effects, and strong links to yield performance, making them strong selection parameters in early vegetative screens (Moragues et al, 2006;Golkar, 2011;Yeilaghi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, by analyzing altered expression of various genes involved in N uptake, assimilation and remobilization along with studying the convergences of proteins and other metabolites during N starvation may provide more insights. Additionally, machine learning for highthroughput stress phenotyping tools will further advance our understandings of NUE trait in other cultivars along with rice [50]. S1: List of differentially expressed genes (DEGs), differentially alternative spliced (DAS) genes, differentially expressed transcripts (DETs), and differentially transcript usage (DTU) transcripts, in genotype, tissues and condition dependent comparative analysis, Table S2: Significant isoform switches among different samples, Table S3: Statistics of significant differentially expressed genes (DEGs), and differentially alternative spliced (DAS) genes, identified in genotype, tissues and condition dependent comparative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, by analyzing altered expression of various genes involved in N uptake, assimilation and remobilization along with studying the convergences of proteins and other metabolites during N starvation may provide more insights. Additionally, machine learning for high-throughput stress phenotyping tools will further advance our understandings of NUE trait in other cultivars along with rice [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…An alternative method is HTP using various spectral cameras. These techniques can effectively evaluate the growth, biophysical, and biochemical performance of plants [115] and will help reduce the cost of phenotyping and improve breeding value prediction accuracy for forest trees.…”
Section: Importance Of Age-related Phenotypingmentioning
confidence: 99%